The Future of Jambi UMKM Marketing Trough The Green Economy in Digital Marketing - Pratiwi, Heni; Hutabarat, Zuhri Saputra (Information Technology and Science (ITScience), 2024)
Advances in digital technology have an impact on business development UMKM. Currently, more and more UMKM are concerned with sustainability by emphasizing their environmentally friendly products. UMKM are one solution to encourage acceleration green economy. Using environmentally friendly products can help reduce negative impact on the environment and climate, while digital business can help accelerate thegrowth of UMKM by expanding market reach. The problem that arises now is that there are still very few UMKM make optimal use of technology in the product promotion process and open up new opportunities for Jambi UMKM in their marketing. First, UMKM are able to differentiate themselves from competitors by offering environmentally friendly products and services. In an increasingly competitive market, UMKM that implement green economic practices have a competitive advantage. Second, society is increasingly aware of the importance of supporting environmentally responsible businesses. By implementing a green economy, UMKM can improve their brand image as companies that care about the environment. Third, consumers are increasingly inclined to choose environmentally friendly products and services. By implementing green economic practices, UMKM in Jambi can attract consumers who care about the environment and have a tendency to choose sustainable products.